The effect of frequency of calcium hydroxide dressing change and various pre- and inter-operative factors on the endodontic treatment of traumatized immature permanent incisors - Yassen, Ghaeth H.; Chin, Judith; Mohammedsharif, Ahmed G.; Alsoufy, Saif S.; Othman, Samer S.; Eckert, George (Dental traumatology, 2012)
–  Aim:  The objectives of this clinical study were as follows: (i) to determine the effect of frequency of calcium hydroxide [Ca(OH)2] dressing change on the apical barrier formation in immature permanent incisors with necrotic pulps and (ii) to investigate the effect of various clinical factors before and during treatment that may be associated with the frequency of Ca(OH)2 dressing changes. Methods:  The study involved 21 healthy subjects, 8–12 years old. Twenty‐three immature traumatized permanent maxillary central incisors were treated using Ca(OH)2 powder mixed with barium sulfate and distilled water. The progress of barrier formation was reviewed after 6 months of first placement of Ca(OH)2 and then every 3 months until the detection of an apical barrier. Clinical and radiographic evaluations were performed before and after treatment. Data were evaluated using a chi‐square test. Results:  Apical barrier formation was successful for all 23 teeth. Seventeen teeth (74%) needed only a single application of Ca(OH)2, while six teeth (26%) required more than one application. The average time of apical barrier formation was 30 weeks, and the mean number of Ca(OH)2 dressing changes was 1.3. A significant positive association was found between teeth that presented with displacement and the number of Ca(OH)2 dressing changes (P = 0.004). Conclusion:  An initial 6‐month application of Ca(OH)2 dressing followed by 3‐month replacements (usually in teeth presenting with displacement and/or sinus tracts) may be successfully used in apexification treatment. This would assist in reducing the number of Ca(OH)2 dressing changes, number of appointments, cost of treatment and radiation exposure.